The The effect of records management on the effectiveness of human resource performance in public services - Hendrawan, Muhammad Rosyihan; Mat Isa, Azman; Samsudin, Ahmad Zam Hariro (Record and Library Journal, 2025)
Background of the study: Records management plays a vital role in supporting administrative performance, particularly human resource effectiveness, in public service institutions. However, inadequate records management practices in local government offices, especially in developing regions, can hinder service delivery, transparency, and accountability. Purpose: This study aims to examine the effect of records management on the effectiveness of human resource performance within the Sawahlunto Municipality Office of Population and Civil Registration in Indonesia. Method: A quantitative explanatory approach was adopted, using a saturated sampling technique involving 75 respondents. Data was collected through structured questionnaires. Inferential analysis using simple linear regression showed a moderate positive relationship and a coefficient of determination, indicating that records management accounts for 14% of the variation in human resource performance. Findings: The findings emphasize that digitalization, record classification, and staff training significantly enhance administrative speed and productivity. While records management is not the sole determinant of human resource performance, it functions as a strategic enabler. Conclusion: The study supports institutional reform efforts by highlighting the importance of integrated records management systems in improving public sector human resource outcomes.